Clinical Practice Guideline for Gastritis in Korea - Seung Joo Kang; Jae Gyu Kim; Hee Seok Moon; Myeong-Cherl Kook; Jong Yeul Lee; Chang Seok Bang; Chung Hyun Tae; Eun Jeong Gong; Su Youn Nam; Hyun Jung Kim (Yong Chan Lee, 2024)
Gastritis is a disease characterized by inflammation of the gastric mucosa. It is very common and has various classification systems such as the updated Sydney system. As there is a lot of evidence that Helicobacter pylori infection is associated with the development of gastric cancer and that gastric cancer can be prevented by eradication, H. pylori gastritis has been emphasized recently. The incidence rate of gastric cancer in Korea is the highest in the world, and due to the spread of screening endoscopy, atrophic gastritis and intestinal metaplasia are commonly diagnosed in the general population. However, there have been no clinical guidelines developed in Korea for these lesions. Therefore, this clinical guideline has been developed by the Korean College of Helicobacter and Upper Gastrointestinal Research for important topics that are frequently encountered in clinical situations related to gastritis. Evidence-based guidelines were developed through systematic review and de novo processes, and eight recommendations were made for eight key questions. This guideline needs to be periodically revised according to the needs of clinical practice or as important evidence about this issue is published in the future.